Communication from the Governor relative to the Virginia State Line with accompanying documents : February 7, 1863 - Richardson, William H. (William Harvie), 1795-1876 (Document (Virginia. General Assembly. Senate) ;, 1863)
February 7, 1863 Communication of Governor Letcher regarding the transfer of the troops of the Virginia State Line to the Confederate government, along with relevant documents.